Analyzing the gender influence on the interest in engineering and technical subjects - Mouronte-López, Mary Luz; García, Arturo; Bautista, Susana; Cortés, Carmen (International journal of technology and design education, 2021)
This paper studies the impact of gender on the interest in engineering and technical subjects of the students in the first courses of secondary education. A statistical analysis was carried out, analyzing the use of a free virtual-reality application, developed by the 3M Foundation, which aims to bring these subjects to the students. Non-parametric statistical methods were used to analyze several variables, such as repetition of the experience, new learning and knowledge reinforcement as well as learning in different ways, which were collected through two questionnaires. These were Pre and Post the playing of the game and later, subsequently validated. This analysis demonstrated that gender has an impact on the interest of the students in engineering and technology but it does not have any influence on the rest of the studied variables. The results show that the interest of girls could be increased through group activities. Age has only influence on the desire to repeat the experience, with a varied level of influence, in the case of the technological contents. The motivational factors that have a greater influence on each variable, “innovation” and “usefulness”, were also analyzed.